In-Vitro Evaluation Of Novel Synthetic Compounds Against Xanthomonas Campestris Pv. Campestris - VINOD KUMAR SEWARIYA; RICHA SHRIVASTAVA; GBKS PRASAD; KISHOR ARORA (International Journal of Pharma and Bio Sciences, 2012)
The present paper discusses studies related to synthetic organic compounds against a Bacterial plant pathogen (Xanthomonas campestris pv. campestris - ITCC) strain isolated from cabbage leaves, a causative of black rot disease on crucifers. In order to achieve the goal of the present studies, solutions of total seven Pyrazolones and Pyridines and three Schiff bases in Di-Methyl formamide (DMF) were evaluated in-vitro against this pathogen using disc diffusion method on nutrient agar and nutrient broth media. These compounds were established on the basis of conventional methods viz. m. pt., elemental analysis and with the help of advanced spectroscopic techniques viz. I.R., NMR and Mass spectral analysis. The pyridine based compounds were found superior to other compounds being studied. Two compounds viz., 3-methyl-1-Phenyl-5-pyrazolone (C5) and 2-Benzyl Pyridine (C10) recorded significant anti-microbial activity against Xanthomonas campestris pv. campestris in-vitro with minimum inhibitory concentration (MIC) of 5 mg/10 mL of the solvent. The observed lab activities of the compounds under study against the pathogen were subjected to Structure Activity Relationship (SAR) studies correlating structural parameters viz. Heat of formation (HF), Zero point energy (ZPE) Dipole moment (DM), Hydration energy (HE), Refractivity (RF), Polarizability (PZ), Surface area (approx) (SAA), Surface area (Grid), (SAG) and Volume (VOL) of the compounds obtained from computational HYPERCHEM Professional software. The observed SAR equations which are significant statistically are also reported. The whole in-vitro antibacterial study was focused to find out the solution for pest management of phytopathogen - Xanthomonas campestris pv. campestris on local area crops of crucifers including Mustard.